2007
DOI: 10.1161/circulationaha.106.662080
|View full text |Cite
|
Sign up to set email alerts
|

Lactadherin Deficiency Leads to Apoptotic Cell Accumulation and Accelerated Atherosclerosis in Mice

Abstract: Background— Atherosclerosis is an immunoinflammatory disease; however, the key factors responsible for the maintenance of immune regulation in a proinflammatory milieu are poorly understood. Methods and Results— Here, we show that milk fat globule-EGF factor 8 (Mfge8, also known as lactadherin) is expressed in normal and atherosclerotic human arteries and is involved in phagocytic clearance of apoptotic cells by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
194
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(204 citation statements)
references
References 51 publications
6
194
1
3
Order By: Relevance
“…Mfge8 can regulate the differentiation of naive T cells into regulatory T cells (Tregs) and Th1 and Th17 cells (14)(15)(16). Each of these cell types has defined roles in asthma (17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…Mfge8 can regulate the differentiation of naive T cells into regulatory T cells (Tregs) and Th1 and Th17 cells (14)(15)(16). Each of these cell types has defined roles in asthma (17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…Tregs dampen the activity of effector T cells, and thus prevent excessive immune reactions, such as autoimmunity, but they can also prevent efficient immune responses, especially in the context of tumors. Two recent articles have proposed a regulatory T cell-promoting role for Mfge8/lactadherin in mice: in atherosclerosis (Ait-Oufella et al, 2007), or in granulocyte monocyte-colony stimulating factor-dependent induction of anti-tumor immune responses (Jinushi et al, 2007). More recently, the latter group has shown that subcutaneous grafts of mouse melanoma cells transfected with Mfge8 were infiltrated with Mfge8-expressing macrophages, regulatory T cells, and poorly efficient cytotoxic T cells when transplanted in mice (Jinushi et al, 2008), and thus became more aggressive.…”
Section: Discussionmentioning
confidence: 99%
“…The MFG-E8 production from macrophages is increased by granulocyte/monocyte colony-stimulating factor (27,29) and fractalkine (CX 3 CL1) (30,31). Furthermore, it is reported that MFG-E8 expression, which is evaluated in human and animal models, is downregulated in some disease conditions such as autoimmune disease (14), Alzheimer disease (32), atherosclerosis (33), acute colitis (20), sepsis (10,31,(34)(35)(36) and I/R injury (37,38). However, in contrast, MFG-E8 is highly expressed in systemic lupus erythematosus (39), lung fibrosis (40), breast cancer (19) and melanoma (41).…”
Section: Mfg-e8 Structure and Productionmentioning
confidence: 99%